Purely Infinite, Simple C^*-Algebras Arising from Free Product Constructions, II - Dykema, Kenneth J. (MATHEMATICA SCANDINAVICA, 2002)
Certain reduced free products of C^*-algebras with respect to faithful states are simple and purely infinite.